Greater cognitive decline with aging among elders with high serum concentrations of organochlorine pesticides. - Se-A Kim (PLoS ONE, 2015)
Although cognitive decline is very common in elders, age-related cognitive decline substantially differs among elders and the determinants of the differences in age-related cognitive decline are unclear. We investigated our hypothesis that the association between age and cognition was stronger in those with higher serum concentrations of organochlorine (OC) pesticides, common persistent and strongly lipophilic neurotoxic chemicals. Participants were 644 elders aged 60-85, participating in the National Health and Nutrition Examination Survey 1999-2002. Six OC pesticides (p,p'-dichlorodiphenyltrichloroethane (DDT), p,p'-dichlorodipenyldichloroethylene (DDE), β-hexachlorocyclohexane, trans-nonachlor, oxychlordane, and heptachlor epoxide) were evaluated. "Lower cognitive function" was defined as having a low Digit-Symbol Substitution Test (DSST) score (<25th percentile of DSST score, cutpoint 28 symbols substituted). Higher levels of β-hexachlorocyclohexane, trans-nonachlor, oxychlordane, and heptachlor epoxide modified the associations between age and lower cognitive function (Pinteraction<0.01, 0.03, <0.01, and 0.02, respectively). Elders in the 3rd tertile of these chemicals demonstrated a greater risk of lower cognitive function with aging, compared to those in the combined 1st and 2nd tertiles. Among those with highest OC pesticides (3rd tertile), the odds ratio for the risk of lower cognitive function was about 6 to 11 for the highest quintile of age (80-85 years) vs. the first quintile of age (60-63 years), while the association between age and lower cognitive function became flatter in those with lower OC pesticides (combined 1st and 2nd tertiles). Both DDT and DDE showed no interaction, with lower DSST scores for higher age irrespective of serum concentrations of DDT or DDE. Even though DSST score measures only one aspect of cognition, several OC pesticides modified aging-related prevalence of low cognitive score, a finding which should be evaluated in prospective studies.